2015
DOI: 10.1021/bi501092p
|View full text |Cite
|
Sign up to set email alerts
|

The Lys-Specific Molecular Tweezer, CLR01, Modulates Aggregation of the Mutant p53 DNA Binding Domain and Inhibits Its Toxicity

Abstract: The tumor suppressor p53 plays a unique role as a central hub of numerous cell proliferation and apoptotic pathways and its malfunction due to mutations is a major cause of various malignancies. Therefore, it serves as an attractive target for developing novel anti-cancer therapeutics. Due to its intrinsically unstable DNA-binding domain, p53 unfolds rapidly at physiological temperature. Certain mutants shift the equilibrium towards the unfolded state and yield high-molecular-weight, non-functional, and cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…Whereas CLR01 induced rapid formation of p53 aggregates of intermediate sizes, it inhibited additional p53 aggregation and reduced the cytotoxicity of the amyloid aggregates (Herzog et al 2015). To some extent, this behavior is similar to that found for the PrP protein, in which some compounds, such as polyanions, stimulate or inhibit aggregation depending on the condition (Gomes et al 2008;Silva et al 2008;Vieira et al 2014).…”
Section: New Approaches For Cancer Therapy Involving P53 Aggregation supporting
confidence: 73%
See 1 more Smart Citation
“…Whereas CLR01 induced rapid formation of p53 aggregates of intermediate sizes, it inhibited additional p53 aggregation and reduced the cytotoxicity of the amyloid aggregates (Herzog et al 2015). To some extent, this behavior is similar to that found for the PrP protein, in which some compounds, such as polyanions, stimulate or inhibit aggregation depending on the condition (Gomes et al 2008;Silva et al 2008;Vieira et al 2014).…”
Section: New Approaches For Cancer Therapy Involving P53 Aggregation supporting
confidence: 73%
“…In a recent study, a protein assembly modulator (CLR01) showed an intriguing effect on p53 DNA-binding domain aggregation (Herzog et al 2015). Whereas CLR01 induced rapid formation of p53 aggregates of intermediate sizes, it inhibited additional p53 aggregation and reduced the cytotoxicity of the amyloid aggregates (Herzog et al 2015).…”
Section: New Approaches For Cancer Therapy Involving P53 Aggregation mentioning
confidence: 99%
“…In differentiated PC-12 cells, no toxicity was observed up to 200 μM and ~15% reduced viability (MTT assay) occurred at 400 μM. 36 No reduction in viability (XTT assay) was found up to 100 μM in human H1299 non-small cell lung carcinoma cells 82 and up to 500 μM in the HIV reporter cell line TZM-bl. 40 …”
Section: Molecular Tweezers Modulate Abnormal Protein Aggregationmentioning
confidence: 96%
“…Partially disordered Ab oligomers formed in the presence of polyphenols were non-toxic [31,136,137], whereas more structured Ab oligomers were toxic. Lysine-binding small molecules ('molecular tweezers') were shown to promote formation of non-toxic oligomers from a variety of amyloidogenic proteins and peptides [138][139][140][141][142] by modulating the oligomer structure. In case of Ab, they have been shown to compact the structures of dimers and tetramers and prevented formation of more toxic higher-order oligomers [143].…”
Section: Relationship Between Oligomer Structure and Cytotoxicitymentioning
confidence: 99%